Pay gaps and outside wages: The U.S. gender wage gap 1980-2010 - Chris Bidner; Ben Sand (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We consider the role of differences in outside wages-the wages earned by similar workers in other jobs-in shaping pay differentials, focusing on the gender dimension in the U.S. during 1980-2010. Using instruments that exploit differential exposure to common industry wage shocks, we find a substantial role for outside wages. Differences in outside wages account for one-half of the level of, and trends in, the unexplained gender wage gap. Our results offer a reinterpretation of trends in the gender wage gap, and suggest that standard wage decompositions are systematically misleading.
Keywords: 330; Wage structure; Gender discrimination; Labor; USA; Lohnstruktur; Geschlechterdiskriminierung; Arbeit; USA